The Effects of Facebook on Students’ Social Life: A Case Study at Mirwais Khan Nika Zabul Institute of Higher Education, Zabul - Himat, Abdul Nafi (American International Journal of Social Science Research, 2020)
In the world, Facebook is one of the most well-known social networking sites, which is used a lot among students. The purpose of this research is to identify the devoted time students’ spend on the usage of Facebook, and its impacts on learners’ social life at Mirwais Khan Nika Zabul Institute of Higher Education, Zabul, Afghanistan. In this study, the quantitative research method was used to collect data from one hundred and fifteen students, and they were selected through a random sample. Likewise, the questionnaire was designed based on the literature review then the data was collected from the participants. Similarly, the data was analyzed by using IBM 24 version of SPSS and found out the frequency and percentage of the demographic data as well as the items. Also, the findings of this research illustrate that learners were devoted from half to one-hour time for using Facebook. Moreover, the results assert that learners want to maintain in connection with people, feel fine when they share their ideas on Facebook and it had positive effects on students’ social life.